Rhubarb extract prevents hepatic inflammation induced by acute alcohol intake, an effect related to the modulation of the gut microbiota. Issue 1 (1st June 2016) - Neyrinck, Audrey M.; Etxeberria, Usune; Taminiau, Bernard; Daube, Georges; Van Hul, Matthias; Everard, Amandine; Cani, Patrice D.; Bindels, Laure B.; Delzenne, Nathalie M.
Abstract : Rhubarb extract induces profound changes in gut microbial composition and down‐regulates acute alcohol‐induced inflammatory and oxidative stresses in the liver of mice. We hypothesize that the increase in specific bacteria by rhubarb extract protects against hepatic damage by reinforcing gut barrier functions. Adapted with permission from Servier MedicalArt (http://creativecommons.org/licenses/by/3.0/legalcode ). Abstract : Scope: Binge consumption of alcohol is an alarming global health problem. Acute ethanol intoxication is characterized by hepatic inflammation and oxidative stress, which could be promoted by gut barrier function alterations. In this study, we have tested the hypothesis of the hepatoprotective effect of rhubarb extract in a mouse model of binge drinking and we explored the contribution of the gut microbiota in the related metabolic effects. Methods and results: Mice were fed a control diet supplemented with or without 0.3% rhubarb extract for 17 days and were necropsied 6 h after an alcohol challenge. Supplementation with rhubarb extract changed the microbial ecosystem (assessed by 16S rDNA pyrosequencing) in favor of Akkermansia muciniphila and Parabacteroides goldsteinii . Furthermore, it improved alcohol‐induced hepatic injury, downregulated key markers of both inflammatory and oxidative stresses in the liver tissue, without affecting significantly steatosis. In the gut, rhubarb supplementation increased crypt depth, tissue weight, and the expression of antimicrobial peptides. Conclusions: These findings suggest that some bacterial genders involved in gut barrier function, are promoted by phytochemicals present in rhubarb extract, and could therefore be involved in the modulation of the susceptibility to hepatic diseases linked to acute alcohol consumption.